Response of a submerged floating tunnel subject to flow-induced vibration - Zou, P.X.; Bricker, Jeremy D.; Chen, L.Z.; Uijttewaal, Wim S.J.; Simao Ferreira, Carlos (Engineering structures, 2022)
•Multi-scale hydrodynamic models combined with the finite element analysis are proposed to predict dynamic response behavior of the submerged floating tunnel.•A typical long SFT coupling tube-joint-mooring components model with a large aspect ratio is simulated in time-domain.•Flow-induced vibrations of the submerged floating tunnel are numerically predicted under currents, waves, and extreme events.•A parametric cross-section for an SFT is recommended due to effectively reduced dynamic response. In order to assess the dynamic performance of a submerged floating tunnel (SFT) subject to flow-induced vibration (FIV) conditions in a practical engineering application, a one-way fluid–structure interaction (FSI) model consisting of multi-scale hydrodynamic solvers combined with the finite element method (FEM) is established. A typical long, large aspect ratio SFT is modeled by coupling tube, joint, and mooring components. The SFT is simulated in the time domain under currents, waves, and extreme events. FIV of SFTs with different cross-section shapes is investigated by analyzing each structure’s natural frequencies, hydraulic loading frequency, and dominant modes. The results show that FIV of the SFT tube is dominated by wave conditions. The excitation of the SFT’s first dominant mode by a large wave height and period should be avoided. Standing and traveling wave patterns and multi-mode response are observed during extreme events. The hydrodynamic forcing and structural dynamic response of the SFT can be effectively reduced by adopting a parametric cross-section.